Kualitas Diet Ibu Hamil Anemia dan Non Anemia - Kusumawati, Dewi; Khoirunnisa, Rissa; Muhlishoh, Arwin (JURNAL RISET GIZI, 2025)
Background: The incidence of anemia in pregnant women in Indonesia is still relatively high which has an impact on mothers and babies born. One of the causes of anemia in pregnancy is the inappropriate quantity and quality of diet.Objectives: This study aims to determine differences in the quality of the diet of anemic and non-anemic pregnant women.Methods: Observational study with a case control design. The sample population taken in this study were pregnant women with as many as 80 people. The number of samples was 54 pregnant women divided into 27 anemia groups and 27 non-anemic groups using purposive sampling technique. The time of research was September 2022 â€“ February 2023. The instrument in this study was the Semi Quantitative-Food Frequency Questionnaire (SQ-FFQ), the Diet Quality Index (DQI) form. Data analysis used the Mann Whitney test.Â Results: The study showed that the average score for quality of diet in the anemic group was 52.18% (low), in the non-anemic group it was 65.48% (good). There were differences in the components of variation in the two groups (p=0.015). There were differences in the adequacy and moderation components in the two groups (p=0.000). There was no difference in the overall balance component in the two groups (p=1.000). There was a difference in the score of the quality of the diet for the anemic and non-anemic groups (p=0.000).Conclusions: There are differences in the quality of the diet of pregnant women in the anemic and non-anemic groups. In anemic pregnant women, the quality of the diet is lower than in non-anemic pregnant women. Pregnant women are expected to improve the quality of the diet consumed in order to achieve optimal health.